Students’ Code-Switching between Selayar Language and English in English Classroom Activities - Syahruni Ramadani; Mustika; Muliadi; Pajri (CV. Eureka Murakabi Abadi, 2026)
This study investigates the students’ code-switching between Selayar language and English during English classroom activities. The research aims to identify the types of code-switching used by students and explore the factors influencing its use in the English classroom. This study employs a qualitative research approach with a descriptive design. The participants are students of a junior secondary school in Selayar, selected purposively. Data are collected through classroom observations, audio recordings of classroom interactions, and interviews. The data are analyzed using thematic analysis to identify patterns and categories of code-switching practices. The findings show that students frequently use inter-sentential and intra-sentential code-switching during classroom interactions. Code-switching occurs due to several factors, including limited English proficiency, the influence of the first language, the need for clarification, and social interaction among peers. Code-switching also helps students maintain interaction during classroom activities, especially when they experience difficulty expressing ideas in English. The study concludes that code-switching plays an important role in facilitating students’ understanding and participation in English classroom activities. This study suggests that teachers should manage code-switching strategically in the English classroom.